Comparison of the production performance of some phenotypic groups and their crosses of quail birds - Tawfeq, Esraa Mobasher (Journal of agricultural, environmental and veterinary sciences, 2024)
The study aimed to determine the production efficiency of local quail phenotypic groups with different feather colors (white, brown, and desert) and their crosses. The results showed significant differences between groups in average body weight at 2, 4, and 6 weeks of age, and in weight gain at 2 and 4 weeks of age in favor of the T6 cross followed by the T5 cross, while T1 recorded the lowest body weight and weight gain compared to other hybrids. Significant differences in feed consumption were observed at 2 and 6 weeks, with no significant differences at 4 weeks. The highest feed consumption was recorded at 6 weeks for hybrids compared to pure groups, and feed conversion efficiency improved at 2 weeks for T5 and T6. At 4 weeks of age, T5, T7, and T6 recorded the best feed conversion efficiency. Positive heterosis in weight at 4 weeks was observed in favor of T5, T6, and T7, while it was negative in T4. Body weight at 6 weeks increased in hybrids T5, T6, and T7 compared to their expected value in the parental groups, and feed conversion efficiency improved at 6 weeks in hybrids T4 and T7. We conclude that heterosis increases the economic value of hybrids, with T6 and T5 being the best hybrids.